Analysis Level of Accountability, Transparency and Community Participation on the Effectiveness Management of Regional Head Election Grants at the General Election Commission Work Unit - Olina Theresia; Ramdany Ramdany; Etty Puji Lestari (Budapest International Research and Critics Institute (BIRCI-Journal): Humanities and Social Sciences, 2021)
This study aimed to analyze the effect of accountability, transparency and public participation on the effectiveness of grants elections local in-unit Election Commission work. The population in this study were all treasurers appointed by the General Elections Commission. Research This Is descriptive quantitative research with analysis method Multiple Linear Regression using SPSS software. The results of this study indicate that the level of accountability partially has a significant effect on the effectiveness of the management of grant funds. Transparency partially does not significantly affect the effectiveness of the management of grant funds. Partial community participation has a significant effect on the effectiveness of the management of grant funds. The level of accountability, transparency and community participation simultaneously has a significant effect on the management of grant funds.